A Editora Guaíra: estratégias, sociabilidades e projetos políticos culturais (décadas de 1930/1940) - Gomes, Gilvana de Fátima Figueiredo [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
A pesquisa investiga a trajetória da Editora Guaíra (Curitiba) e de se proprietário, Oscar Joseph De Plácido e Silva. Com base em recursos metodológicos da História dos Livros e da História Intelectual, analisa-se o processo de formação profissional do editor Oscar Joseph, bem como seu ingresso no mercado editorial nacional, a partir de 1930. As estratégias utilizadas pelo empresário para superar o isolamento geográfico articuladas à complexa rede de relações constituída, principalmente, por sujeitos que se afirmavam como uma nova geração – intelectual e política – delinearam o perfil da Editora Guaíra. A análise das sociabilidades intelectuais e das coleções que ocuparam lugar central no catálogo da empresa, revelam os projetos políticos e culturais abrigados pela editora; além disso, permitem compreender parte dos deslocamentos intelectuais ocorridos no período.

The research investigates the trajectory of Editora Guaíra (Curitiba) and of its owner, Oscar Joseph De Plácido e Silva. With basis on methodological resources from the History of Books and Intellectual History, the process of professional qualification of editor Oscar Joseph is analyzed, as well as his entry in the national publishing market, from 1930 on. The strategies used by the entrepreneur to overcome geographic isolation articulated to the complex network of relations constituted, mostly, by subjects who asserted themselves as a new generation - intellectual and political - delineated the profile of Editora Guaíra. The analysis of intellectual sociability and the collections that occupied a central place in the company's catalog, reveal the political and cultural projects sheltered by the publishing company; moreover, they make it possible to understand part of the intellectual displacements that occurred in the period.
Editora Guaíra: Strategies, sociability and political-cultural projects (1930s / 1940s)
Keywords: Editora Guaíra; História Editorial; História da literatura; História dos livros no Brasil; Intelectuais; Editorial History; History of books in Brazil; History of literature; Intellectuals